Thrips of the Frankliniella minuta group (Insecta: Thysanoptera) in Costa Rican Asteraceae flowers - Retana, Axel (Universidad de Costa Rica, 1994)
Six new species of the genus Frankliniella minuta group are described, al! from Costa Rican Asteraceae, and mainly from high altitudes: Frankliniella kiesteri, Fr. hansoni, Fr. vargasi, Fr. cotobrusensis, Fr. zurqui and Fr. montanosa. A diagnosis of the genus is given and the minuta group is redefined; according lo the new definition Frankliniella diversa and Frankliniella bagnalliana are included in this species group. A key to eleven species for 11 species is presented